2019
DOI: 10.1103/physrevd.99.023520
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear anisotropy growth in Bianchi-I spacetime in metric f(R) cosmology

Abstract: The present work is related to anisotropic cosmological evolution in metric f (R) theory of gravity. The initial part of the paper develops the general cosmological dynamics of homogeneous anisotropic Bianchi-I spacetime in f (R) cosmology. The anisotropic spacetime is pervaded by a barotropic fluid which has isotropic pressure. The paper predicts nonlinear growth of anisotropy in such spacetimes. In the later part of the paper we display the predictive power of the nonlinear differential equation responsible … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…We do not set a lower limit for the spin periods. We use the standard expression B P 2 = 0.17 × 10 12 G s −2 (4) (Ruderman & Sutherlandt 1975;Bhattacharya et al 1992) for the pulsar death line. Note that the exact location of the death line is still under debate (see, e.g., Zhang et al 2000;Zhang 2002;Zhou et al 2017).…”
Section: Magnetic Field and Spin-period Evolutionmentioning
confidence: 99%
“…We do not set a lower limit for the spin periods. We use the standard expression B P 2 = 0.17 × 10 12 G s −2 (4) (Ruderman & Sutherlandt 1975;Bhattacharya et al 1992) for the pulsar death line. Note that the exact location of the death line is still under debate (see, e.g., Zhang et al 2000;Zhang 2002;Zhou et al 2017).…”
Section: Magnetic Field and Spin-period Evolutionmentioning
confidence: 99%
“…The dynamics of the Bianchi-I metric (12) under f (R) gravity in presence of such an isotropic fluid can be described by the following set of equations [40,41],…”
Section: Isotropic Fluidmentioning
confidence: 99%
“…where δ · β ′ is defined analogously to (26), instead of (39) and (40). Again, given some form of the function f (R), we can find the Einstein frame scalar field potential V (φ) by using Eq.…”
Section: Anisotropic Fluidmentioning
confidence: 99%
“…They also argued that this may be due to scattering from large scale inhomogeneities in the line of sight to the pulsar. Bhattacharya et al (1992) fitted a broken power-law (sum of two power-laws) to the τ sc −DM relation, since they saw a flattening from a simple power-law spectrum at low DMs (below a DM of ∼30 pc cm −3 ). Their fit showed that the measured τ sc follows Kolmogorov turbulence at low DMs and deviates at higher DMs.…”
Section: Dm Dependence Of Scatteringmentioning
confidence: 99%
“…Thus, we chose 200 MHz as a reference frequency for comparison of different models. The model relations we chose from the literature are (1) a simple power law model (Slee et al 1980;Alurkar, Slee & Bobra 1986), (2) a broken power law model as in Equation 4, (3) a broken power law model by fixing the value of ζ = 2.2 in Equation 4 (Bhattacharya et al 1992;Ramachandran et al 1997), and (4) a second order polynomial fit following Bhat et al (2004) as given in Equation 5. Since we measured α for the pulsars used in this study, we have scaled τ sc using it and removed the last term in Equation 5 while fitting (Lewandowski et al 2015a;Geyer et al 2017).…”
Section: Dm Dependence Of Scatteringmentioning
confidence: 99%